Pouzdanost i validnost procene osnovnih kinematickih i karakteristika sile vuce kod plivaca primenom testa plivanija u mestu maksimalnim intenzitetom u trjanju 60 sekundi - Dopsaj, M.; Matkovic, I.; Thanopoulos, V.; Okcic, T. (Facta Universitatis: Series Physical Education and Sport, 2003)
The subject of this paper is to define a reliability of the test for the estimation of basic kinematics and mechanical characteristics of pulling force in swimmers measured by the method of tethered swimming with maximum intensity of 60 seconds. The sample was composed of 10 categorized senior age swimmers. All swimmers were specialists in sprint and middle distance crawl techniques (50, 100, 200 and 400m).Testing was administered by tensiometric probe with the hardware-software logistics support by test-retest method. Kinematics characteristics were given in two variables (AVG STROKE 60 TS Time - average stroke duration and AVG HZ 60 TS - realized stroke frequency) while pulling force characteristics were given in five variables (AVG F max 60 TS - average of maximum pulling force (peaks) of individual strokes, AVG F min 60 TS - average of minimal pulling force of the individual strokes, AVG F 60 TS - average of pulling force of the individual strokes, AVG Imp F 60 TS - average of impulses of pulling force of the individual strokes and AVG RFD 60 TS - average rate of force development of the pulling force in individual strokes. On the basis of the obtained results we can conclude that the given estimation method is generally valid on the level of Crombach's alpha = 0.8694, is generally reliable on the level of Spearman-Brown's rtt = 0.9722 (97.22%) and is generally factor valid on the level of 0.929 to 0.938 (92.8 to 93.8%) so it can be recommended for further use in sports practice. In respect to the observed partial indicators i.e. individual variables it was found out that the variables AVG RFD 60 TS, AVG Stroke 60 TS Time, AVG HZ 60 TS, AVG F max 60 TS, AFG F min 60 TS and AVG F 60 TS are statistically significant and valid in the range of 0.777 to 0.979 and reliable in the range of 0.782 to 0.979 respectively. The variable AVG Imp 60 TS in this research was not either sufficiently valid - 0.518 or reliable - 0.641. Since the general level of validity and reliability is very high and statistically significant we can assume that the insufficient level of partial validity and reliability of - AVG Imp F 60 TS variable is rather a consequence of relatively small sample (10 subjects) than the real measuring characteristics of the given variable.